Prosedur Pengeluaran Kas Di Lp3i Karawang - Nurul Wildani, Ismy; Usmar, Andi; Desty Puspatriani, Annisa (POLITEKNIK LP3I, 2025)
The research outlined in this final project aims to examine the application of cash disbursement procedures at LP3I Karawang and its suitability to the Flow Chart according to Mulyadi. The research method used is a qualitative descriptive method that describes the Cash Disbursement Procedure at LP3I Karawang. The data collection techniques used by researchers are interviews, observation, documentation and literature study. In the implementation of the cash disbursement procedure at LP3I Karawang, there are several obstacles and efforts including: The lack of orderly application for funds which should always end at 15.00 is overcome by imposing the rules for applying for funds only until 15.00 unless there is a special promise, There is still a lack of cash checks at LP3I Karawang is overcome by cash opname every day. Then they still often hold funds for more than 3 days. After analyzing and discussing the problem, the author concludes that the implementation of the cash disbursement procedure at LP3I Karawang is quite good, because there are still several functions that are combined and the recording is still lacking in detail.